Pengaruh Financial Distress dan Profitabilitas terhadap Audit Report Lag - Mutiara Lusiana Annisa, Mutiara Lusiana Annisa (P3M Politeknik Negeri Bengkalis, 2024)
The aim of this research is to analyze the influence of financial distress and profitability on audit report lag in companies listed on the Jakarta Islamic Index. Secondary data was used in this study. The data was obtained from the official Stockbit and BEI websites, namely www.stockbit.com and www.idx.co.id, as well as journal references that support this research. The population in this study consists of all companies listed on the Jakarta Islamic Index from 2020 to 2023. Over a four-year period, from 2020 to 2023, a purposive sampling technique was applied, resulting in a sample of 6 companies and 24 observations. Logistic regression was utilized to analyze the data, with the assistance of the SPSS program. The results of the study indicate that (1) financial distress, when examined partially, does not have a significant effect on audit report lag, and (2) profitability, when examined partially, does not have a significant effect on audit quality. This research has important implications for company management. Companies experiencing financial distress should enhance their financial reporting systems. Additionally, improving coordination with auditors is essential to ensure the audit process is completed on time. Strong profitability can serve as a factor in attracting high-quality auditors. By doing so, the risk of audit delays can be minimized. For auditors, this research provides insights into identifying factors that can cause delays in the audit process. This knowledge is valuable for helping auditors allocate resources more efficiently. It is particularly important for companies experiencing financial distress.